Effects of concurrent training sequence on VO2max and lower limb strength performance: A systematic review and meta-analysis - Gao, Jiuxiang; Yu, Liang (Frontiers in Physiology, 2023)
The aim of this study is to compare the effects of concurrent strength and endurance training sequences on VO2max and lower limb strength performance to provide scientific guidance for training practice. We searched PubMed, EBSCO, Web of Science (WOS), Wanfang, and China National Knowledge Infrastructure (CNKI) databases up to December 2022. The included articles were randomized controlled trials that allowed us to compare the strength–endurance (S-E) sequence and endurance–strength (E-S) sequence on VO2max, maximum knee extension strength, maximum knee flexion strength, and lower limb power. The Cochrane bias risk tool was used to evaluate the methodological quality of the included literature, and Stata 12.0 was used for the heterogeneity test, subgroup analysis, draw forest map, sensitivity analysis, and publication bias evaluation. The results have been presented as standardized mean differences (SMDs) between treatments with 95% confidence intervals and calculations performed using random effects models. Significance was accepted when p < 0.05. The studies included 19 randomized controlled trials (285 males and 197 females), 242 subjects in S-E sequence, and 240 subjects in E-S sequence in the analyses. No difference changes between S-E and E-S sequences has been observed on VO2max in the overall analysis (SMD = 0.02, 95% CI: −0.21–0.25, p = 0.859). The S-E sequence shows a greater increase in lower limb strength performance than does the E-S sequence (SMD = 0.19, 95% CI: 0.02–0.37, p = 0.032), which was manifested in the elderly (p = 0.039) and women (p = 0.017); in training periods >8 weeks (p = 0.002) and training frequencies twice a week (p = 0.003); and with maximum knee flexion (p = 0.040) and knee extension strength (p = 0.026), while no difference was found in lower limb power (p = 0.523). In conclusion, the effect of VO2max will not change with different concurrent training sequences. The S-E sequence improves lower limb strength more significantly, mainly in the improvement of knee flexion and knee extension. This advantage is more related to factors such as age, gender, training period, and training frequency.